2022
DOI: 10.4103/aer.aer_123_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pericapsular nerve group block with fascia iliaca compartment block in adult patients undergoing hip surgeries: A double-blinded randomized control study

Abstract: Background: Hip fractures are the most common orthopedic condition in elderly patients. In this patient group, efficient preoperative analgesia that reduces the requirement for opioids and their negative side effects is crucial. This study aims for evaluating the efficiency of fascia iliaca compartment block (FICB) and pericapsular nerve group (PENG) in providing the appropriate analgesia before positioning patients for spinal anesthesia (SA). Methods: Ninety participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Following the search, we initially identified 2960 studies; no additional records were found through other sources. We reviewed 984 full texts and included 12 RCTs[ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 23 ] in the analysis [ Figure 1 ]. These RCTs included 644 participants, 326 who underwent PENG block and 318 who received FICB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the search, we initially identified 2960 studies; no additional records were found through other sources. We reviewed 984 full texts and included 12 RCTs[ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 23 ] in the analysis [ Figure 1 ]. These RCTs included 644 participants, 326 who underwent PENG block and 318 who received FICB.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] Two studies used ropivacaine 0.5% for both blocks[ 6 , 8 ]; however, one study used ropivacaine 0.4% for both blocks,[ 5 ] and one study used ropivacaine 0.25% for both blocks. [ 10 ] Three studies used bupivacaine 0.25% for both blocks[ 7 , 13 , 23 ]; however, one study used levobupivacaine 0.25% with dexamethasone 4 mg as an adjuvant for both blocks,[ 9 ] one study used 0.25% bupivacaine with 1 µg/kg clonidine[ 12 ] and another study used 0.375% ropivacaine. [ 11 ] The patients who were a part of the studies had ages ranging from 50 years to 74 years on average.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For primary total hip arthroplasty, the pericapsular nerve group block results in the better preservation of the motor function than the fascia iliaca block [34]. Also, as seen in table 3, the PENG block outperformed the fascia iliaca block in providing adequate analgesia before positioning patients undergoing hip surgery under spinal anesthesia [37], which is especially important in patients undergoing hip surgery due to fracture [35].…”
Section: The Peng Block Vs the Fascia Iliaca Blockmentioning
confidence: 97%